University Students’ Readiness towards Mobile Learning: The Stages of Change Model - Mehreen Azam; Salman Bin Naeem; Rubina Bhatti (Pakistan Journal of Information Management & Libraries, 2021)
Information seeking modes are changing rapidly due to advancements in portable devices such as smartphones. The functionality of smartphones is helping individuals to enhance their online learning experiences. The study was conducted to assess the readiness level among students towards the adoption of mobile learning at The Islamia University of Bahawalpur. A survey method of research was used to collect data for this study. A self-administered questionnaire was distributed through convenience sampling among the enrolled students of The Islamia University of Bahawalpur. Of the 183 respondents, the majority of 118 (64.5%) were female. Overwhelming, 170 (92.9%) respondents' usage frequency was 'daily' for accessing information through mobile. Stages of change model indicated that most of the respondents were at the 'maintenance stage' indicating that they were regularly using mobile for learning. The main barriers to mobile learning included: 'mobile learning causes sore eyes', and 'mobile screen size makes it difficult to concentrate on contents. The study concluded that a high level of readiness exists among students towards adopting mobile learning as they are regularly using smartphones to access the information from online resources to fulfill the requirements of formal learning. A statistically significant difference was found in the readiness level as female students are more likely to adopt m-learning than male students. The study's findings are useful for librarians, faculty members, IT experts, and policymakers of the participating university in designing mobile-related services for students to enhance learning communications and collaborations.